Management Information System Design Hospital Health Services Using Scrum - Surya Mahendra, I Gusti Ngurah Agung; Mahadya Suta, Ida Bagus Leo; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
The standard of health services for health providers is to provide maximum service to patients. Based on the Ministry of Health Number: 129 / Menkes / SK / II / 2008 the waiting time of patients is approximately 60 minutes so we can assume that the management of the average time in the field is 15 minutes the process of retrieving queue numbers, 40 minutes waiting time and checking patients and 25 minutes time prescription retrieval at the pharmacy, with the translation of the allocation time we can develop an Agile development system with Scrum framework. Development using Scrum framework itself is used to overcome the problems of development time and human resources so that the results obtained can be evaluated to determine the level of functionality and effectiveness of the system in terms of user satisfaction and increase the quality of service providers and medical personnel.